2021
DOI: 10.1080/08897077.2021.1915918
|View full text |Cite
|
Sign up to set email alerts
|

Opioid Stewardship Training during the Transition to Residency to Prepare Medical Students to Recognize and Treat Opioid use Disorder

Abstract: Background: With a drastic shortage of addiction medicine specialists-and an ever-growing number of patients with opioid use disorder (OUD)-there is a dire need for more clinicians to feel confident in prevention and management of OUD and obtain a DEA-X waiver to prescribe medications to treat OUD. Here we determine if it is feasible to certify 4th year medical students with DEA-X waiver training as a component of the PROUD (Prevent and Reduce Opioid Use Disorder) curriculum, and if PROUD enhanced preparedness… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 16 publications
(25 reference statements)
0
6
0
Order By: Relevance
“…Many also included additional items related to OUD, such as opioid epidemic, racial/ethnicity and disparity in opioid epidemic, social stigma towards OUD, social barriers in treatment of patients with pain and/or OUD, and relevant law and regulations. Four programs used Drug Addiction Treatment Act of 2000 (DATA 2000) waiver trainings developed either by professional organizations or in-house ( 29 32 ). However, despite the recognition of the contribution from comorbid psychiatric disorders and relevant social factors, none of these articles mentioned specifically the use of biopsychosocial approaches in their curricula.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Many also included additional items related to OUD, such as opioid epidemic, racial/ethnicity and disparity in opioid epidemic, social stigma towards OUD, social barriers in treatment of patients with pain and/or OUD, and relevant law and regulations. Four programs used Drug Addiction Treatment Act of 2000 (DATA 2000) waiver trainings developed either by professional organizations or in-house ( 29 32 ). However, despite the recognition of the contribution from comorbid psychiatric disorders and relevant social factors, none of these articles mentioned specifically the use of biopsychosocial approaches in their curricula.…”
Section: Resultsmentioning
confidence: 99%
“…However, despite the recognition of the contribution from comorbid psychiatric disorders and relevant social factors, none of these articles mentioned specifically the use of biopsychosocial approaches in their curricula. Further, only 3 out of the 17 studied curricula mentioned pain in their major topic areas and the pain topic had a limited focus on managing pain in patient with OUD ( 29 , 30 , 33 ). In addition, a small number of programs focused on students' clinical skills, such as team-based practice, motivational interview and application of SBIRT (Screening, Brief Intervention, and Referral to Treatment), patient screening and education ( 34 36 ).…”
Section: Resultsmentioning
confidence: 99%
“… 26 , 27 Dedicated curricular time for opioid stewardship and buprenorphine waiver training during this transition has been shown to improve knowledge and is associated with high satisfaction among students. 23 Other studies have shown that brief sessions can lead to improved learning and learner satisfaction in medical training. 28 , 29 Our research similarly suggests that the Transition to Residency course may be an opportune setting for a brief, high-yield training covering many of the same topics but requiring less curricular time than formal X-waiver training, depending on the needs of the specific program.…”
Section: Discussionmentioning
confidence: 99%
“…They saw knowledge gains, high course satisfaction, and that students reported timing of the course was optimal. 23 In their study, they included pre- and post- knowledge asessments and a survey 3 months into intern year; in the future our group hopes to implement these methods.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Zerbo and colleagues implemented a DATA waiver training with 4th year medical students with results showing 6-months post training statistically significant increases from their pre-tests in both knowledge and confidence with MOUD treatment, and an increase from baseline in reported likelihood to prescribe buprenorphine for OUD treatment [ 14 ]. Another program implementing the DATA waiver training with 4th year students showed similar increases in knowledge and feeling more prepared to treat patients with OUD using buprenorphine from pre to posttest [ 15 ]. Initiatives implementing the DATA wavier training with 3rd year medical students curricula shows similar positive results.…”
Section: Discussionmentioning
confidence: 99%